ARTIFICIAL INTELLIGENCE AS BRAND CREATOR AND INFRINGER: A CRITICAL LITERATURE REVIEW OF BRAND OWNERSHIP, REGISTRATION AND LEGAL PROTECTION IN THE ERA OF GENERATIVE AI - Gunawan Widjaja (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
Artificial intelligence, particularly generative AI, has transformed the role of brands as human creative products by enabling the automatic creation of names, logos and visual identities. This article examines AI as both a creator and an infringer of brands, focusing on three key aspects: ownership, registration, and legal protection of brands in the era of generative AI. It is analysed that the regulatory framework for brands based on human authorship faces serious challenges when AI output is not fully controlled by humans, thereby raising uncertainties regarding the subject of rights, uniqueness, and the validity of registration. On the other hand, AI also has the potential to be a source of trademark infringement when its outputs resemble or incorporate elements of registered trademarks, whether through data learning processes or irresponsible use, thus requiring a re-evaluation of legal liability and protection mechanisms. This article argues that trademark law needs to evolve towards a more adaptive, responsive, and risk-based approach, so as to accommodate the dynamics of AI without compromising the principles of legal certainty, justice, and the protection of exclusive rights for businesses.